Does family communication moderate the association between adverse childhood experiences and emotional and behavioural problems? - Lackova Rebicova, Miriama; Dankulincova Veselska, Zuzana; Husarova, Daniela; Klein, Daniel; Madarasova Geckova, Andrea; van Dijk, Jitse P; Reijneveld, Sijmen A (BMC public health, 2020)
BACKGROUND: Adverse childhood experiences (ACEs) and poor family support and communication can increase emotional and behavioural problems (EBP). Therefore, we assessed the association of difficult communication with mother and with father separately with both emotional and behavioural problems (EBP), and whether adolescents' communication with mother and with father moderates the association of adverse childhood experiences (ACE) with the EBP of adolescents. METHODS: We used data from the Health Behaviour in School-aged Children study conducted in 2018 in Slovakia, comprising 5202 adolescents aged from 11 to 15 (mean age 13.53; 49.3% boys). EBP were measured using the Strengths and Difficulties Questionnaire. We used generalized linear regression adjusted for age, gender and family affluence to explore the modification of the associations between ACE and EBP by communication (easy vs. difficult communication) with mother and father. RESULTS: Difficult communication or a complete lack of communication due to the absence of mother and father increased the probability of emotional (exp (b): 0.96, 95% CI: 0.92|1.00; and 0.95, 95% CI: 0.91|0.99, respectively) and also of behavioural problems (exp (b): 0.96, 95% CI: 0.92|1.00; and 0.94, 95% CI: 0.90|0.97, respectively). We found a statistically significant interaction of communication with father on the association of ACE with EBP, showing that the joint effects were less than multiplicative. CONCLUSION: Difficult communication with mother and father is related to EBP among adolescents, and adolescents' communication with father moderates the association of ACE with both emotional and behavioural problems among adolescents.
Keywords: Fathers; otcové; komunikace; Parents; Adolescents; vztahy mezi rodiči a dětmi; chování mladistvých; Problem Behavior; mladiství; nepříznivé zkušenosti z dětství; mužské pohlaví; Adverse Childhood Experiences; dítě; Adverse childhood experiences; Child; Slovakia; problémové chování; Mental Disorders; Slovenská republika; ženské pohlaví; Humans; Emotional problems; Communication; emoce; Adolescent Behavior; Parent-Child Relations; duševní poruchy; Emotions; Family communication; Female; Behavioural problems; Adolescent; rodiče; lidé; Male